2021
DOI: 10.1002/cphc.202100370
|View full text |Cite
|
Sign up to set email alerts
|

Real‐Time Fluorescence Visualization of Nanoparticle Aggregation and the Polymorph‐Transition Process of a Mechanofluorochromic Difluoroboron‐β‐Diketone Derivative

Abstract: The use of organic nanomaterials in biomedical and optical devices has been widely studied. The key to improving the performance and stability of these devices is to control the fabrication process, which determines the phase stability and photophysical properties. In this study, fluorescence changes were observed during the reprecipitation process of mechanofluorochromic molecules of dibenzoyl(methanato)boron difluoride. The cyan-emission phase (C-phase) was first identified. The time evolution of the resolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The fluorescence spectra of organic compounds are sensitive to the interactions between two or more molecules and differences in their aggregation states, , which offers the possibility of tracing the crystal formation in solution. We have applied dibenzoylmethanatoboron difluoride derivatives (BF 2 DBM) as probe molecules because of their excellent optical properties, including high fluorescence quantum yield in the solid state and mechanochromic luminescence (MCL) properties. During the evaporative crystallization of 4,4′-di- tert -butyldibenzoylmethanatoboron difluoride, the fluorescence color changed from purple to blue via orange . This phenomenon indicated that crystallization occurred from the dispersed state as a monomer through intermediate states (e.g., liquid-like clusters or dense droplets), demonstrating a successful two-step nucleation process for fluorescence visualization. , During the solvent evaporation crystallization of BF 2 DBM, the amorphous-like intermediates that transiently appeared were a precursor to crystal nuclei observed only in the supersaturation region.…”
Section: Introductionmentioning
confidence: 99%
“…The fluorescence spectra of organic compounds are sensitive to the interactions between two or more molecules and differences in their aggregation states, , which offers the possibility of tracing the crystal formation in solution. We have applied dibenzoylmethanatoboron difluoride derivatives (BF 2 DBM) as probe molecules because of their excellent optical properties, including high fluorescence quantum yield in the solid state and mechanochromic luminescence (MCL) properties. During the evaporative crystallization of 4,4′-di- tert -butyldibenzoylmethanatoboron difluoride, the fluorescence color changed from purple to blue via orange . This phenomenon indicated that crystallization occurred from the dispersed state as a monomer through intermediate states (e.g., liquid-like clusters or dense droplets), demonstrating a successful two-step nucleation process for fluorescence visualization. , During the solvent evaporation crystallization of BF 2 DBM, the amorphous-like intermediates that transiently appeared were a precursor to crystal nuclei observed only in the supersaturation region.…”
Section: Introductionmentioning
confidence: 99%
“…As a probe molecule, we have previously applied dibenzoylmethanatoboron difluoride derivatives (BF 2 DBM), which have excellent optical properties, such as high fluorescence quantum yield in the solid-state and mechanofluorochromic properties . In particular, the fluorescence color and spectral changes, which depend on the aggregation form, enable direct fluorescence visualization during evaporative crystallization. Observing the evaporative crystallization of 4,4′-di tert -butyldibenzoylmethanatoboron difluoride (BF 2 DBMb, Figure a), it was found that the fluorescence color changes from purple to blue via orange. This phenomenon indicates that crystallization occurs from dispersed states as monomers via an intermediate state (such as liquid-like clusters or high-density droplets), demonstrating that we succeeded in fluorescence visualization of the TSN model during solvent evaporation. , …”
Section: Introductionmentioning
confidence: 99%
“…58,59 This rule is historically for solid crystals, and to our knowledge it has been applied to organic dye aggregates only a few times. 89,93,102,103…”
Section: Resultsmentioning
confidence: 99%
“…58,59 This rule is historically for solid crystals, and to our knowledge it has been applied to organic dye aggregates only a few times. 89,93,102,103 Ostwald's rule of stages only predicts the initial and final states of a substance; no details are given about the path that connects the two. Careful inspection of the scattering com- ponent of the absorbance at 700 nm over time hints at just such a path.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation